2016
DOI: 10.1016/j.scitotenv.2015.06.143
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and risk of pharmaceuticals in freshwater systems are related to the population density and the livestock units in Iberian Rivers

Abstract: Considerable amounts of pharmaceuticals are used in human and veterinary medicine, which are not efficiently removed during wastewater and slurries treatment and subsequently entering continuously into freshwater systems. The intrinsic biological activity of these non-regulated pollutants turns their presence in the aquatic environment into an ecological matter of concern. We present the first quantitative study relating the presence of pharmaceuticals and their predicted ecotoxicological effects with human po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(68 citation statements)
references
References 52 publications
3
53
0
12
Order By: Relevance
“…Recent in vivo and in vitro studies with PPCPs have indicated that CbE activity can be modulated by a broad range of chemicals as it participates in its metabolism and detoxification reactions and can also be inhibited in vitro by lipid regulators as it occurs in humans (Ribalta et al 2015;Solé et al 2014;Solé and Sanchez-Hernandez 2015). Many of these chemicals are found in the watercourse of the Ebre river (Lopez-Serna et al 2012;Osorio et al 2016). Although the individual levels detected are not likely to be responsible for the significant inhibition observed, the consequences derived from cocktail mixtures are not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent in vivo and in vitro studies with PPCPs have indicated that CbE activity can be modulated by a broad range of chemicals as it participates in its metabolism and detoxification reactions and can also be inhibited in vitro by lipid regulators as it occurs in humans (Ribalta et al 2015;Solé et al 2014;Solé and Sanchez-Hernandez 2015). Many of these chemicals are found in the watercourse of the Ebre river (Lopez-Serna et al 2012;Osorio et al 2016). Although the individual levels detected are not likely to be responsible for the significant inhibition observed, the consequences derived from cocktail mixtures are not known.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, important phase I reactions involved in xenobiotic metabolism-EROD, BFCOD and CbE activities-were screened for the potential interaction of PPCPs of environmental concern that can be found in the river basin (Fabrega et al 2013;Osorio et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These results further suggest that the reservoir may have a potency to regulate the migration and transformation of antibiotics. On the other hand, compared to the pristine reservoir, it also implies that the concentration and distribution of antibiotics in the aquatic environment may be more related to human activities [56]. …”
Section: Relationships Between Basic Parameters and Antibiotic Concenmentioning
confidence: 99%
“…En este orden de ideas, la mala calidad del agua de un río, puede estar asociada a diversos factores de origen antrópico o natural, por ejemplo: escorrentías de zonas agrícolas o pecuarias, el vertimiento de aguas residuales domésticas o industriales o por arrastre de material sólido asociado a eventos climáticos [4] En consecuencia, para estudiar la contaminación de los ríos, se debe considerar las sustancias contaminantes presentes en el agua y los sedimentos, así como los fenómenos de transferencia entre ambas matrices; pues los sedimentos reconcentran sustancias con el transcurso del tiempo, ya que su concentración en el agua es más variable y dinámica [5]- [7] Además, los sedimentos albergan organismos de la cadena trófica que pueden verse afectados por sustancias orgánicas complejas entre las cuales se encuentran ciertos compuestos orgánicos persistentes (COPs) o sus metabolitos que pueden ser tóxicos; por ejemplo: ciertos plaguicidas, compuestos farmacéuticos o retardantes de llama [6]- [10]Así mismo, muchos COPs son altamente hidrofóbicos por lo que su nocividad se debe rastrear en los sedimentos y/o en la biota [8], [11], [12].…”
Section: Introductionunclassified
“…A este respecto, la literatura técnica señala entre otros aspectos, que ciertos COPs como los hidrocarburos aromáticos policíclicos (PAHs), los plaguicidas o los fármacos; y los metales pesados, tienden a fijarse y movilizarse a través de los sedimentos de un río. Asimismo, existe una estrecha relación entre los eventos climáticos y el transporte, destino y transformación de tales sustancias en un río [8], [10], [11] En este contexto, por ejemplo, bajo eventos de lluvias o sequias intensas, los sedimentos pueden transportan contaminantes hacia y desde zonas inundadas o a zonas aguas abajo del río, alejadas de las descargas puntuales. Así, mismo pueden ocurrir diferentes fenómenos de transferencia de masa entre las matrices agua y sedimentos, por ejemplo, aquellos fenómenos relacionados con las características granulométricas de los sedimentos o a las propiedades fisicoquímicas tanto del agua como de los sedientos [8], [13], [14].…”
Section: Introductionunclassified